A comparative survey of reef fishes in Caribbean and Pacific Costa Rica - Phillips, Peter C. (1984)
Fishes from five transects in Manuel Antonio National Park (pacific) and seven transects in Cahuita National Park (Caribbean), Costa Rica were censused using a rapid visual technique from February to April 1982. Cahuita, with 49 species, had a higher overall species diversity, whereas more individuals were usually seen on the Manuel Antonio transects, where 39 species were counted. Transects with similar habitat complexity showed highest PS values (approximately 60%). Wrasses (Labridae) and damselfish (Pomacentridae) dominated in both the Pacific rock reef and the Caribbean coral reef study areas. Individuals up to 7.5 cm usually dominated on transects, but an increase in size was observed as the habitat complexity increased. Diversity was low at Cahuita in relation to other Caribbean reef areas, probably due to the declining state of the coral reef. The species diversity values at Manuel Antonio are within the range of values found in Central American Pacific estuarine and tidepool studies.